(untitled) (Research, Society and Development, 2020)
High School is the final stage of Basic Education, with a minimum duration of three years, which begins after the end of Elementary School. The objective of this work is to demonstrate the school performance rates (pass, fail and drop out), in High School, in the States of the Northern Region, in the period from 2012 to 2016. Methodologically, this research has a qualitative approach, with a subtle bias quantitative, but without the use of strict statistical criteria. Quantitative data were consulted in the database of the Brazilian Institute of Geography and Statistics (IBGE). The results, in the period studied, show an increase in approvals. The failure rate is practically stable in the first three years (close to 11%), falling in 2015 (1.5%) and rising in the following year above the level (close to 13%). The rate remains stable in the first four years of the period, dropping in 2016. Variations in school performance rates in high school can be explained through aspects related to school infrastructure, valuing education professionals and the student’s personal motivation.